PRACTICE BEYOND INSTRUCTION: EXPLORING PRACTICE STRATEGIES IN PRIMARY SCHOOL DRUM LEARNING - Sembiring, Piter; Latifah, Diah; Gunara, Sandie (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2026)
This study addresses the limited attention given to independent practice in primary music education by examining how young students structure drum practice beyond direct instruction in a non-formal setting. A qualitative design was employed involving four students aged seven to nine, using participant observation, semi-structured interviews, and document analysis during thirty-minute sessions. Inductive thematic analysis revealed that students consistently initiated practice by revisiting previously learned 4/4 grooves, using prior material as a structural anchor. Despite tempo instability and coordination challenges between the hi-hat and bass drum, students maintained rhythmic coherence while negotiating motor demands. Problem-solving was predominantly global, relying on whole-pattern repetition rather than segmentation. Practice organization emerged implicitly, progressing from hi-hat stabilization toward full groove integration. These findings highlight early-stage self-structured practice behaviors and extend understanding of independent practice in drum learning. However, the small sample and single-context design limit generalizability. Future research should involve larger samples and longitudinal approaches to examine developmental progression in practice strategies.